Diagnosis and risk stratification of chest pain patients in the emergency department: focus on acute coronary syndromes. A position paper of the Acute Cardiovascular Care Association. Issue 1 (1st February 2020) - Stepinska, Janina; Lettino, Maddelena; Ahrens, Ingo; Bueno, Hector; Garcia-Castrillo, Luis; Khoury, Abdo; Lancellotti, Patrizio; Mueller, Christian; Muenzel, Thomas; Oleksiak, Anna; Petrino, Roberta; Guimenez, Maria Rubini; et al.
Abstract: This paper provides an update on the European Society of Cardiology task force report on the management of chest pain. Its main purpose is to provide an update on the decision algorithms and diagnostic pathways to be used in the emergency department for the assessment and triage of patients with chest pain symptoms suggestive of acute coronary syndromes.